Probiotic in productive behaviour, biochemical and hematological changes and intestinal health of laying quails - Vega-Vega, Vicente (2016)
This study evaluated the productive behavior, biochemical changes, hematological and intestinal health of quails (Coturnix coturnix japonica), its effect was determined in egg production, egg weight, feed conversion, histology of the duodenum portion of the small intestine and hematological and biochemical blood levels. For this study 320 Quails spread over four treatments (0, 125, 250, 375 g of probiotic Avi-bac) with four replications of 20 birds were used. The experiment lasted 30 days. Randomized complete block design was used and means were analyzed by the Tukey test. The results of the productive variables showed no significant difference (p> 0.05), as the villi of the duodenum portion of hematology and blood biochemistry.